PENGARUH CORPORATE SOSIAL RESPONSIBILITY TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SYARIAH - Nadya, Galuh Raina; Mai, Muhamad Umar; Setiawan, Setiawan (Politeknik Negeri Jakarta, 2020)
The purpose of this study is to investigate how the influence of corporate social responsibility towards the corporate performance in general, and the influence of each subject of the corporate social responsibility. Corporate social responsibility is company’s activities in achieving a balance or integrations between the economic, social, and environment development without compromising the expectations of shareholder (obtain profit). In this research corporate performance measured by ROE (return on equity). The samples used in this study are all manufacturing companies enrolled in Indeks Saham Syariah Indonesia listing in 2017 and published the annual report in 2017 by using method of purposive judgement sampling. There are 87 companies that meet the criteria of the study sample. The analysis method used is path analysis. Data collection method used in this research is a method of documentation and literature study method. The results of this study indicate that the disclosure of CSR as in general has a significant effect on the performance of the company with a positive traits. Disclosure of CSR in the economic subject has no significant effect on company performance. Disclosure of CSR in the Environment has a significant effect on the performance of companies with positive traits. Disclosure of CSR in the Social subject has a significant effect on the performance of the company with a positive traits.